Transformation of Islamic Education Management Based on Qur’anic Organizational Culture to Enhance Institutional Global Competitiveness - Ahd. Mujahid; Abu Siri; Harun Ar-Rasyid (Institut Bahri Asyiq Galis Bangkalan, 2025)
This study was motivated by the increasing demand for global competitiveness among Islamic educational institutions amid the dynamics of globalization, digital transformation, and international academic quality competition. Many institutions have undertaken administrative modernization; however, they have not fully integrated Qur’anic values as a strategic foundation of organizational culture. This study aimed to analyze the transformation of Islamic education management based on Qur’anic organizational culture and its implications for enhancing institutional global competitiveness. A descriptive qualitative approach was employed using a Systematic Literature Review design of scholarly articles published between 2016 and 2025, retrieved from Scopus, Google Scholar, and Sinta databases. Data were analyzed through content analysis and thematic analysis to systematically synthesize cross-study findings. The results indicated that the internalization of the values of trustworthiness, excellence, consultation, and justice within managerial systems contributed to strengthening governance quality, institutional reputation, and strategic sustainability. This study offered theoretical contributions by integrating organizational culture theory with the paradigm of Islamic education management and practical contributions through a value-based transformation model to enhance institutional global competitiveness.